(untitled) (Research, Society and Development, 2022)
The purpose of this study is to describe the potentialities, frailties and suggestions in the nurses’ perceptions regarding the assistance delivered by a Rapid Response Team (RRT). This is an exploratory study with quanti-qualitative approach. The study was conducted with 22 nurses from public teaching hospital in the states of Paraná, Brazil. The results displayed the following potentialities: rapid care of RRT when requested in clinical and surgical care units for adult and improvement of health care assistance delivered to patients. As frailties, the participants mentioned lack of assistance during the night shifts, lack of communications between the RRT and the nurse in-charge of the ward, among others. Participants suggested an exclusive nurse to assist the team, periodical service meetings, among others. We hope the results of this study may contribute to build an innovative service by discussing the process of health care assistance delivered to a patient that becomes critic during hospitalization.